CHALLENGES AND SOLUTIONS FOR LAWYERS AS LEGAL ENFORCERS IN CRIMINAL CASES (A STUDY IN LEGAL PSYCHOLOGY) - Alwi Jaya; Gustika Sandra; Tarmizi Tarmizi; Asia Asia (Cerdika: Jurnal Ilmiah Indonesia, 2021)
In reality, lawyers as Legal Enforcers in Criminal Cases still face obstacles, both internally and externally. Therefore, efforts to optimize the role of lawyers in criminal cases involve providing services to the public without discrimination. This research uses a descriptive juridical method. The results of this study indicate that efforts that can be made to optimize the implementation of the lawyer's function in criminal cases are as follows: Lawyers must be aware of and fulfill their primary duties and functions in providing legal assistance to the public without discrimination. Law Enforcement Officials (Police, Prosecutors, Judges) as legal enforcement partners should provide positive support to lawyers so that they can fulfill their primary duties and functions in providing legal assistance to the public without discrimination.